Socialism : A Very Short Introduction - Newman, Michael (Karachi, Pakistan Oxford University Press, 2007)
Offering a practical and historical perspective on socialism this work explains the evolution of socialist ideas from the French Revolution, and examines why past attempts to implement socialism might have failed.
Include Index
Keywords: Socialism -- POLITICAL SCIENCE -- Political Ideologies -- Communism & Socialism